Plastic anisotropy and twin distributions near the fatigue crack tip of textured Mg alloys from in situ synchrotron X-ray diffraction measurements and multiscale mechanics modeling. (August 2022) - Xie, Di; Zhang, Wei; Lyu, Zongyang; Liaw, Peter K.; Tran, Huy; Chew, Huck Beng; Wei, Yujie; Ren, Yang; Gao, Yanfei
Abstract: In spite of many potential applications due to their superior mechanical properties, magnesium alloys still find many practical restrictions primarily due to our limited knowledge of their failure mechanisms. In situ and non-destructive strain measurements on the microstructural scales are critical in understanding the fatigue crack behavior, which has greater advantages than the macroscopic measurements based on replica technique and the small-scale mechanical testing that cannot easily provide a complete view on the synergy of many scale-dependent deformation and failure mechanisms. This work exploits the state-of-the-art synchrotron X-ray diffraction technique to attain in situ strain mapping results, with high spatial resolution, near a fatigue crack tip in the highly textured ZK60 Mg alloy. The accurate measurements in the plastic zone are compared to a micromechanical modeling framework, in which the steady fatigue crack is simulated by an irreversible, hysteretic cohesive interface model and the surrounding plasticity by Hill anisotropic plasticity. The general agreement in the anisotropic deformation fields is reached down to half of the plastic zone size towards the crack tip, while the discrepancy right at the crack tip can be used to develop an inverse model to extract the material-specific fatigue damage evolution in our future work. It is surprisingly noted that twin activities are localized in a narrow band from the tip to the wake of the fatigue crack, irrespective of the crack growth direction of this textured alloy. Such twin-crack interactions are understood here by our crystal plasticity finite element simulations with several representative crystallographic orientations.